Sosialisasi Peningkatan Kesadaran Dan Kepatuhan Pajak Kendaraan Di UPTD PPD Seluma - Fitri, Dwi Kusmita; Susanti, Neri; Anggriani, Ida; Fitriano, Yun (Jurnal Dehasen Mengabdi, 2024)
The vehicle tax awareness campaign at UPTD PPD Kabupaten Seluma aims to increase public awareness and compliance in paying vehicle taxes. The methods used include direct counseling sessions, leaflet distribution, and pre-post campaign surveys. The results show a significant increase in public understanding and awareness of the importance of paying vehicle taxes. Active community participation and positive responses to the presented materials confirm the effectiveness of the campaign. Recommendations include the need for continuous and intensified campaigns, the use of more engaging educational media, participatory approaches, optimization of social media, and strengthening cooperation with related agencies. Thus, it is expected that increased public awareness and compliance can support regional revenue growth and contribute to community development and welfare.